2016
DOI: 10.2134/agronj2015.0119
|View full text |Cite
|
Sign up to set email alerts
|

Brassica Cover Crop Effects on Nitrogen Availability and Oat and Corn Yield

Abstract: Cover crops are used to scavenge residual soil nitrate, with the goal of reducing N losses from agricultural fields and increasing subsequent N availability. Two experiments were conducted to determine fall‐planted brassica cover crops’ effect on N availability for rotational crops. The first evaluated five species—brown mustard [Brassica juncea (L.) Czern], hybrid turnip (Brassica rapa L. × B. napus L.), radish (Raphanus sativus L.), rapeseed (Brassica napus L.), and white mustard (Sinapis alba L.)—in rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
(41 reference statements)
2
13
1
Order By: Relevance
“…This confirms findings by Gieske et al. () and Munkholm and Hansen () that radish can substantially reduce the soil mineral N content in late autumn, compared with bare soil. In three of the 6 years in the present study, the significant difference derived from the subsoil samples (30–60 cm), not the topsoil (0–30 cm), while in the other 3 years both soil depth contributed equally (Figure b).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This confirms findings by Gieske et al. () and Munkholm and Hansen () that radish can substantially reduce the soil mineral N content in late autumn, compared with bare soil. In three of the 6 years in the present study, the significant difference derived from the subsoil samples (30–60 cm), not the topsoil (0–30 cm), while in the other 3 years both soil depth contributed equally (Figure b).…”
Section: Resultssupporting
confidence: 92%
“…Gieske et al. () observed that radish cover crop increased the yield of oats grown in the following year, but concluded that this effect was not linked to increased N availability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapeseed, as a cover crop, has many potential benefits (Chen et al 2007;Chen and Weil 2010;Gieske et al 2016;Virginia NRCS 2015;Williams and Weil 2004). However, termination can be difficult, as demonstrated in these experiments and reported by growers.…”
Section: Virginia 2017mentioning
confidence: 85%
“…The rapeseed taproot is cylindrical and fast-growing, allowing it to act as a "biodrill" that can reach one or more meters into the soil (Virginia NRCS 2015). Producers in the midwestern United States utilize brassica species to scavenge residual nitrogen left after cash crop harvest (Gieske et al 2016). Gieske et al (2016) found that brown mustard (Brassica juncea L.), rapeseed, radish (Raphanus sativus L.), and white mustard (Sinapis alba L.) all accumulate comparable amounts of nitrogen and biomass.…”
Section: Introductionmentioning
confidence: 99%